The Musical Structure and Meaning of Go Laba in the Context of People’s Life Philosophy in Ngadha Culture, Flores, East Nusa Tenggara - Dopo, Florentianus; Sukmayadi, Yudi (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
Art is an integral aspect of culture. Almost all aspects of human life are always wrapped in some form of art. Indonesia is a country that has diverse artistic expressions. Different from Western arts that emphasize the element of aesthetics, traditional arts in various cultures in the Eastern world display elements that are more than just aesthetics. Other intended elements include the values or the life philosophy of the owner community. Traditional music always has two components that can not be separated from one another: textual and contextual aspects. Understanding a musical tradition should cover both aspects in their entirety. This paper aims to expose the contextual aspects of a musical tradition of Ngadha, Flores, NTT called go laba. The contextual aspect in question is the values or life philosophy of the community represented through this traditional music.